Analysis of pollution load on the oxygen distribution at Segment Sumbersari – Kaliwater Segment of Bedadung River, Jember Regency - Novita, Elida; Afi Dhea Septian; Hendra Andiananta Pradana, (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Bedadung River is one of the main rivers in Jember Regency. Along with the river flow of the Sumbersari Subdistrict and Kaliwates Subdistricts, there is an anthropogenic activity in the form of densely populated housing and agricultural land that produces organic and inorganic waste. Such activities that are directly related to the river have the potential to increase the burden of pollution. The resulting pollution load can potentially lower water quality. The purpose of this study is to analyze the water quality and the rate of deoxygenation and reoxygenation of the Bedadung River Segment Sumbersari-Kaliwates District using the Streeter-Phelps method. Data collection in the form of water debit, TSS, DO, BOD, and COD with grab sampling. The results of the calculation of the rate of deoxygenation and reoxygenation are synthesized using quantitative descriptive methods. The TSS and DO values ​​meet the grade I quality standard but the BOD and COD values ​​do not meet the grade I quality standard. The mean deoxygenation rate (rD) and reoxygenation (rR) were 0.798 mg/L.day and 2.753 mg/L.day, respectively. The value of the reoxygenation rate is greater than the value of the deoxygenation rate. These conditions indicate that the Bedadung River's ability to perform well in reducing organic matter naturally. The size of rR and rD is influenced by the reoxygenation constant, deoxygenation constant, and the hydraulic profile of the river.